Fire Risk Assessment in an Educational Environment using the Fire Risk Assessment Method for Engineers (Shahid Sadoughi University of Medical Sciences, 2020)
Abstract Background and Aim: This study tried to assess the risk level of fire in an educational environment by Fire Risk Assessment Method for Engineers (FRAME) software using a practical method. Furthermore, some effective strategies were proposed to reduce the risk level of fire and increase security in the environment. Methods: In this practical study, the fire risk assessment was assessed in an educational environment by FRAME. This risk assessment was done in three sections including building and contents, residents, and activities. It was tried to gain the highest fire security for the educational environment using practical and logical control measures. The required data were collected by studying and monitoring the situation, observing, interviewing, referring to the available documents, measuring some parameters, and using regulatory inventory and checklists according to the requirements of the FRAME executive instruction. The data were analyzed using FRAME. Results: based on the findings, the risk level of fire for the educational environment was at an unfavorable level in residents (R=2.7) and activities' (R=3.8) section. However, some parts such as laboratories, libraries, and partitioning units in the building section were at a high-risk level (R>1) . Some preventive measures were recommended for reducing the risk level of fire and improving the security of situation by considering some effective criteria in the software.  The results showed a significant reduction in the risk level of fire in all three sections so that they all reach an acceptable level (R< 1). Conclusion: The FRAME method can assess and determine the quantity of risk level and provide the suitable controlling methods to improve fire security in the educational environments by considering the opportunities and challenges of the existing environment.